The deubiquitinase USP22 regulates PD-L1 degradation in human cancer cells - Wang, Yu (Cell Commun Signal, 2020)
BACKGROUND: Many cancers evade immune surveillance by overexpressing PD-L1. PD-L1 interacted with its receptor PD-1, resulting in reduction of T cell proliferation and activation and thereafter cancer cell death mediated by T-lymphocyte. Understanding the mechanisms that regulate PD-L1 was of vital importance for immune checkpoint blockade therapy (ICBT). METHODS: Human non-small cell lung cancer cells and 293FT cells were used to investigate the function of USP22 upon PD-L1 and CSN5 by WB, Immunoprecipitation, Immunofluorescence and Flow cytometry analysis. B16-F10 cells were used to explore the role of USP22 on tumorigenesis and T cell cytotoxicity. The relationship between USP22 and PD-L1 expression was investigated by Immunohistochemistry analysis in human non-small cell lung cancer samples. RESULTS: Our data showed that USP22 interacted with PD-L1 and promoted its stability. USP22 deubiquitinated PD-L1 and inhibited its proteasome degradation. Moreover, USP22 also interacted with CSN5 and stabilized CSN5 through deubiquitination. Either USP22 or CSN5 could facilitate the interaction of PD-L1 with the other one. Furthermore, USP22 removed K6, K11, K27, K29, K33 and K63-linked ubiquitin chain of both CSN5 and PD-L1. In addition, USP22 depletion inhibited tumorigenesis and promoted T cell cytotoxicity. Besides, USP22 expression positively correlated with PD-L1 expression in human non-small cell lung cancer samples. CONCLUSIONS: Here, we suggested that USP22 is a new regulator for PD-L1. On the one hand, USP22 could directly regulate PD-L1 stability through deubiquitination. On the other hand, USP22 regulated PD-L1 protein level through USP22-CSN5-PD-L1 axis. In addition, USP22 depletion inhibited tumorigenesis and promoted T cell cytotoxicity. Besides, USP22 expression positively correlated with PD-L1 expression in human non-small cell lung cancer samples. Together, we identified a new regulator of PD-L1 and characterized the important role of USP22 in PD-L1 mediated immune evasion. Targeting USP22 might be a new solution to ICBT. GRAPHICAL ABSTRACT: [Image: see text]